Nuclear Energy Regulation, Risk and The Environment - Al Faruque, Abdullah; Taylor and Francis (Boca Raton, FL : Routledge, 2018)
Analyzing the impact and benefits of nuclear energy on environment, this book examines nuclear treaties in relation to environmental protection, highlights legal framework on non-proliferation and denuclearization, explores treaties on nuclear safety and nuclear security, discusses legal regimes on management of nuclear wastes, assesses the third-party liability regime and discusses the role of IAEA, EURATOM and NEA in regulating nuclear energy. It explores nuclear energy in the context of climate change and sustainable development. This book also examines the international legal framework on notification, assistance and emergency preparedness in the event of nuclear accidents, considers legal aspects of decommissioning of nuclear power plants and main legislative trends on nuclear energy use in selected countries. It also addresses regulatory responses to nuclear energyin the wake ofthe Fukushima power plant nuclear accident in Japan.
Table of Contents -- Preface -- Abbreviations -- List of cases -- List of Instruments -- List of Statutes -- Chapter 1 -- Nuclear Energy in Context -- Chapter 2 -- Theoretical Relationship between International Nuclear Energy Law and Environmental Law -- --Chapter 3 -- Nuclear Accidents and their Environmental Effects -- --Chapter 4 -- Management of Nuclear Wastes -- --Chapter 5 -- Legal Regime on Safety and Security of Nuclear Installations -- --Chapter 6 -- Decommissioning of Nuclear Installations -- Chapter 7 -- Legal Regime on Third Party Nuclear Liability -- --Chapter 8 -- Notification, Emergency Preparedness and Response to Nuclear Accident -- Chapter 9 -- Institutional Framework on Regulation of Nuclear Energy -- --Chapter 10 -- Legislative Trends on Nuclear Energy and Environment in Selected Countries -- Chapter 11 -- Review of Regulatory Responses to Fukushima Incident -- Concluding Remarks -- Bibliography -- Index-- -- --.
Includes bibliographical references and index.
Also available in print format.
Keywords: Nuclear energy -- Law and legislation; Environmental law; Liability for nuclear damages; Radioactive waste disposal -- Law and legislation; Nuclear industry -- Risk management; Nuclear facilities -- Law and legislation; Nuclear power plants -- Safety regulations; Electronic books